Investigation of the food safety of lamb meat obtained in ecologically unfavorable territories - Apsalikova, Zukhra; Amirkhanov, Kumarbek; Gaptar, Svetlana; Mukanova, Alima; Yevlampiyeva, Yelena; Kassymov, Samat; Brait, Yulia; Spanova, Assem; Lipikhina, Aleksandra; Apsalikov, Kazbek (Frontiers in Sustainable Food Systems, 2024)
Introduction This article presents data on the ecological situation of agricultural territories where small cattle are raised, focusing on the exposure dose rate, radon concentration in residential and social buildings, and the density of alpha and beta particle flux. The study also examines the levels of heavy metals (Pb, Cd, As, Hg) and radionuclides Cs-137 and Sr-90 in raw meat from ecologically unfavorable areas, as well as the effects of heat treatment on reducing the content of these harmful substances. Methods The research involved analyzing raw meat samples from the Abai district near the former Semipalatinsk Nuclear Test Site in Semey, Kazakhstan. The levels of heavy metals and radionuclides were measured before and after heat treatment to assess the effectiveness of cooking in reducing these contaminants. Radioecological measurements were also conducted in residential and social buildings to evaluate radon concentration and alpha and beta particle flux. Results and discussion The results of the study showed a significant decrease in the levels of lead, cadmium, arsenic, Cs-137, and Sr-90 in meat after heat treatment. Prolonged cooking or quenching led to the most significant reductions in toxicity and radionuclides. These findings suggest that heat treatment can be an effective method for reducing the levels of harmful substances in meat from ecologically compromised areas. Further research is needed to explore other potential strategies for mitigating the impact of environmental contamination on food safety in agricultural regions.